2010
DOI: 10.1371/journal.pone.0010190
|View full text |Cite
|
Sign up to set email alerts
|

Nicotianamine, a Novel Enhancer of Rice Iron Bioavailability to Humans

Abstract: BackgroundPolished rice is a staple food for over 50% of the world's population, but contains little bioavailable iron (Fe) to meet human needs. Thus, biofortifying the rice grain with novel promoters or enhancers of Fe utilization would be one of the most effective strategies to prevent the high prevalence of Fe deficiency and iron deficiency anemia in the developing world.Methodology/Principal FindingsWe transformed an elite rice line cultivated in Southern China with the rice nicotianamine synthase gene (Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 35 publications
4
114
0
Order By: Relevance
“…Overexpressing NAS gene from barley and rice increased Fe and Zn concentrations by two-to threefolds in transgenic rice compared to WT, with no obvious effect on agronomic traits (Table 3.9). Using Caco-2 cell digest model, Zheng et al (2010) further demonstrated that elevated NA concentration led to more than twofold higher bioavailable Fe from the high NA seeds than the WT. Thus, NA is a novel and effective promoter of Fe utilization.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 94%
See 1 more Smart Citation
“…Overexpressing NAS gene from barley and rice increased Fe and Zn concentrations by two-to threefolds in transgenic rice compared to WT, with no obvious effect on agronomic traits (Table 3.9). Using Caco-2 cell digest model, Zheng et al (2010) further demonstrated that elevated NA concentration led to more than twofold higher bioavailable Fe from the high NA seeds than the WT. Thus, NA is a novel and effective promoter of Fe utilization.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 94%
“…More importantly, the transgenic rice plants containing AtNAS and Pvferritin genes increased seed-Fe concentration by sixfold, with no yield penalty but such plants were earlier to flower, and that the Fe in the endosperm of the transgenic rice lines accumulated in spots, most probably as a consequence of spatially restricted ferritin accumulation (Wirth et al 2009). Biofortifying rice with NAS alone or in combination with ferritin has great potential in combating global human Fe deficiency in people dependent on rice for their sustenance (Lee et al 2009;Zheng et al 2010). Mugineic acid family phytosiderophores (MAs) play an important role in the uptake of Fe from the soil and Fe transport within the plant in graminaceous plants.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…Although the study by Zheng et al (2010) did not focus on enhancing Fe concentrations, that research group did find the bioavailability of Fe to be twice as great as that of the control line, as measured by ferritin synthesis in an in-vitro Caco-2 cell model. We have previously shown that grains from activation-tagged lines of OsNAS3 have 2.9-fold more Fe (Lee et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted expression of Pvferriitn and AtNAS1 improves Fe contents in rice endosperm by more than 6-fold (Wirth et al, 2009). Endosperm-specific expression of OsNAS1 results in a significant rise in NA concentrations in both unpolished and polished grains (Zheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that these transgenic seeds provided a better source of dietary Fe than the wild type seeds (Lee et al, 2009). (Zheng et al, 2010) demonstrated by seed-specific expression of OsNAS1 that rice grains contained a higher amount of nicotianamine. These transgenic rice grains performed better in Fe utilization studies using human cells (Zheng et al, 2010).…”
Section: Increase Of Nicotianamine Contentmentioning
confidence: 99%